Looking East again?: Malaysia-Japan relations in the 21st century - Lai, Yew Meng (Penerbit UMS, 2017)
This article analyses the trends and developments in Malaysia-Japan relations since its inception in 1957. It begins with a brief historical overview of their bilateral interactions, followed by a scrutiny of the developments and shifting trends, from the early decade of the establishment of official diplomatic relations between independent Malaya and Japan that coincided with the Cold War to the introduction of Malaysia’s Look East Policy (LEP) in the early 1980’s that saw Malaysia-Japan ties taking-off to new and unprecedented heights. In doing so, the article reveals the major impetuses/drivers of their ‘special relationship’, which among others include complementarities in their national economies, perceived sociocultural affinities underpinned by the so-called ‘Asian values’ and idiosyncrasies of key leaders like Mahathir Mohamad, as well as the given regional strategic environment, which contributed to a congruence of strategic thought and mutual interests between the major actors from both countries that led to Malaysia’s admirable relations with Japan before the turn of the 21st century. This article also assesses the contemporary trends in and prospects for their bilateral ties, by identifying the changing dynamics that have brought a qualitative shift in the Malaysia-Japan bilateral relationship which is moving towards strategic partnership and beyond.